Mutual Appreciation - Bujalski, Andrew; Grunsky, Matthias; Rice, Justin; Clift, Rachel (Diffusion, 2007)
Andrew Bujalski the brightest new voice in American independent film follows up his critically acclaimed debut "Funny Ha Ha" with a compelling tale of music friendship and love. Alan is an indie singer-songwriter who has just arrived in Brooklyn after the break-up of his band. He has a coveted gig at the hip Northsix club that is being promoted by Sara an enchanting radio DJ who finds him a drummer and who also has designs on Alan. However Alan prefers hanging out with his old friend Lawrence and Lawrence's girlfriend, Ellie. Can Alan make it as a musician, whilst dealing with his dangerous mutual attraction to Ellie? [Cover]
Keywords: DVD-Video